Alcohol and Immediate Risk of Cardiovascular Events: A Systematic Review and Dose–Response Meta-Analysis. Issue 10 (8th March 2016) - Mostofsky, Elizabeth; Chahal, Harpreet S.; Mukamal, Kenneth J.; Rimm, Eric B.; Mittleman, Murray A.
Abstract : Background—: Although considerable research describes the cardiovascular effects of habitual moderate and heavy alcohol consumption, the immediate risks following alcohol intake have not been well characterized. Based on its physiological effects, alcohol may have markedly different effects on immediate and long-term risk. Methods and Results—: We searched CINAHL, Embase, and PubMed from inception to March 12, 2015, supplemented with manual screening for observational studies assessing the association between alcohol intake and cardiovascular events in the following hours and days. We calculated pooled relative risks and 95% confidence intervals for the association between alcohol intake and myocardial infarction, ischemic stroke, and hemorrhagic stroke using DerSimonian and Laird random-effects models to model any alcohol intake or dose–response relationships of alcohol intake and cardiovascular events. Among 1056 citations and 37 full-text articles reviewed, 23 studies (29 457 participants) were included. Moderate alcohol consumption was associated with an immediately higher cardiovascular risk that was attenuated after 24 hours, and even protective for myocardial infarction and hemorrhagic stroke (≈2–4 drinks: relative risk=30% lower risk) and protective against ischemic stroke within 1 week (≈6 drinks: 19% lower risk). In contrast, heavy alcohol drinking was associated with higher cardiovascular risk in the following day (≈6–9 drinks: relative risk=1.3–2.3) and week (≈19–30 drinks: relative risk=2.25–6.2). Conclusions—: There appears to be a consistent finding of an immediately higher cardiovascular risk following any alcohol consumption, but, by 24 hours, only heavy alcohol intake conferred continued risk. Abstract : Supplemental Digital Content is available in the text.